PEMBELAJARAN PENULISAN NASKAH DRAMA BERBASIS PADLET DI KELAS XI SMA PLUS SEDAYU NUSANTARA MEDAN - Widya Arfiyanti Puspa Sari; Panigoran Siburian; Sartika Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The teaching of drama script writing at the high school level is often still conventional and theoretical, resulting in students being less motivated and less actively engaged in the writing process. This study aims to describe the implementation of digital-based learning in drama script writing by utilizing the Padlet application integrated with artificial intelligence (AI) features in Grade XI of SMA Plus Sedayu Nusantara. This research employs a qualitative approach with a descriptive design, conducted directly in the classroom using a Project-Based Learning model. Data were collected through observation, interviews, and documentation of the learning process and students’ works. The results indicate that the use of Padlet and its AI features can enhance students’ creativity, collaboration, and independence in writing drama scripts. Students find it easier to explore ideas, receive instant feedback, and produce more varied and engaging works. Challenges such as limited internet access and initial adaptation to technology can be addressed through intensive guidance and the provision of alternative learning media. This learning model is recommended for wider implementation to support digital literacy and the development of creative writing skills in the era of the Merdeka Curriculum.